Penerapan Home Visit Dalam Meningkatkan Kedisiplinan Siswa di Sekolah SMKN 1 Pulo Ampel - Aminudin; Ramanda, Peni (Universitas Muhammadiyah Makassar, 2025)
This study aims to analyze the implementation of the home visit method in improving student discipline at SMKN 1 Pulo Ampel. The home visit method is applied as a mentoring strategy for students with low discipline levels, involving collaboration between the school, teachers, and parents. This research employs a descriptive qualitative approach, collecting data through observations, interviews, and documentation. The results indicate that the home visit method effectively increases students' awareness of the importance of discipline, strengthens communication between teachers and parents, and creates a more conducive learning environment. In conclusion, the home visit method can serve as an effective alternative for addressing student discipline issues, particularly at the vocational high school level.